The Effect of Leverage on Profitability: A Dynamic Panel Study on the IDX - Wirawan Widjanarko (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The relationship between leverage and profitability still shows diverse empirical results, especially in companies in Indonesia. This study aims to identify the relationship between the degree of financial leverage used and the profitability of companies within the tier structures of the Indonesia Stock Exchange by employing a dynamic econometric model, the Generalized Method of Moments (GMM) Arellano-Bond Approach. This study is based on the published annual reports of sample companies from 2015 to 2024, which provide their financial and operational performance over the study period. In this study, the dynamic panel model is used because it eliminates endogeneity and simultaneity bias in the estimation, which are common in the assessment of leverage and profitability when measured simultaneously, and it also delivers both the short- and long-run impacts of the model’s variables. The findings suggest a negative, significant impact of financial leverage on profitability: profits decrease as a firm’s debt level increases. However, the broader positive effects of profitability and firm size, as well as growth in sales, confirm the relevance of sales magnitude and dynamics in improving the firm’s financial performance. The findings corroborate the Trade-off Theory and indicate that Indonesian manufacturing firms should maintain an appropriate capital structure to improve profitability while minimizing the probability of bankruptcy.